BS55 Regulation of skeletal muscle stem cell function in a mouse model of experimental atherosclerosis and hyperlipidaemia. (May 2019) - Matsakas, Antonios; Barlow, Joseph; Sfyri, Peggy; Verpoorten, Sandrine; Scully, David
Abstract : Introduction: Apolipoprotein E deficient (ApoE KO) mice are an established model of hyperlipidemia and atherosclerosis, which displays increased oxidative stress and triglyceride contents in the skeletal muscle. Experimental evidence suggests that ApoE KO mice have impaired regeneration after injury. Skeletal muscle stem cells are responsible for the regenerative capacity of skeletal muscle and undergo activation, proliferation and differentiation upon injury in order to support muscle repair and regeneration. The skeletal muscle stem cell function of ApoE KO mice remains largely unknown. We hypothesised that the attenuated regenerative capacity of the ApoE-deficient muscle derives from deficits in skeletal muscle stem cell function. Therefore, we investigated the impact of ApoE deficiency on the proliferation and differentiation profiles of muscle stem cells. Methods: Muscle stem cells from the extensor digitorum longus and biceps brachii were isolated from male ApoE KO and wild type mice for single fibre culture experiments ex vivo and stem cell cultures in vitro. Stem cell proliferation and differentiation, morphology, immunohistochemistry and gene expression analysis were performed. Cell culture experiments were conducted with n=6–9 technical replicates and n=2–3 independent experiments. Significant statistical differences were determined by the Mann-Whitney U test for p<0.05. Results: Single fibres of wild type and ApoE KO mice did not markedly differ in their myogenic proliferation over the first 48h in culture. After 72 hours however, impaired differentiation of ApoE KO mouse muscle stem cells was evident on single fibres ex vivo based on reduced expression of the muscle regulatory factor myogenin. Furthermore, treatment of cultures with 0.5mM palmitate for 24h resulted in loss of stemness and increased commitment to differentiation (i.e. Pax7-ve/MyoD+ve cells) as well as increased myogenic differentiation. Isolated muscle stem cells from ApoE KO mouse displayed impaired proliferation as well as differentiation, with morphological studies resulting in reduced myotube width and length, an indicator of reduced myotube fusion. These results were exacerbated by application of palmitate in both wild type and ApoE KO. These findings are strengthened by reduced gene expression data for key factors regulating skeletal muscle fusion of myogenic progenitors, cell fate and contractility (i.e. MyoD, Scrib1, myogenin, Bex1, tmem8c, srf, mhc1 and acta1). Conclusion: We report for the first time impaired skeletal muscle stem cell function in hyperlipidaemic ApoE KO mice, which may account for the impaired regenerative capacity of this mouse strain. These data establish a link between muscle stem biology and impaired myogenesis in an experimental model of atherosclerosis and systemic hyperlipidaemia with implications for the myopathies seen in cardiovascular disorders. Conflict of interest: None